Relational marketing in mass marketing: theory or actual practice? - Wakabayashi, José Luis (2012)
The relational marketing paradigm, as well as its predecessors, has been rapidly added to marketing management’s lexicon and tool kit. In conjunction with this concept, theoreticians have devised techniques that are essential to make it operative. Paramount among them is the development of the client management process and within it, the use and application of the Customer Lifetime Value concept which is the relational approach’s corner stone, and the present value of future growth is generated by clients In working with clients, this is essential to determine the strategy that will allow the company to reach and/or preserve its competitive advantage. Evidence so far suggests that although companies are prone to adopt the relational marketing paradigm, they still enforce transactional marketing concepts. This may be the consequence of the emerging use of that concept and the Customer Lifetime Value technique in Latin American countries as part of the client management process. The failure to use this concept in dynamic industries, as in mass retail, is a topic of interest for administration sciences and in particular, marketing and this article seeks to draw attention to this fact.